(untitled) (Web of Teachers: Inderscience Research, 2023)
This article presents a comprehensive methodology for imparting critical thinking skills to primary school students within the framework of education classes. The methodology integrates innovative pedagogical approaches with established cognitive development theories to cultivate students’ analytical, evaluative, and problem-solving abilities. By focusing on fostering these skills at an early age, educators can enhance students’ cognitive development and equip them with essential tools for lifelong learning.